Molecular Epidemiology and Pathogenic Characterization of Novel Chicken Infectious Anemia Viruses in Henan Province of China - Wang, Xin-Wei; Feng, Jie; Jin, Jia-Xin; Zhu, Xiao-Jing; Sun, Ai-Jun; Liu, Hua-Yuan; Wang, Jing-Jing; Wang, Rui; Yang, Xia; Chen, Lu; Liao, Yi-Fei; Zhuang, Guo-Qing (Frontiers in Veterinary Science, 2022)
Chicken infectious anemia (CIA) is an immunosuppressive disease caused by the chicken infectious anemia virus (CIAV) resulting in heavy economic losses once an outbreak is established. This study conducted a systematic analysis of the epidemiology and pathology of CIA in Henan province, China. A total of 437 clinical tissue samples and 120 poultry disease-related live attenuated vaccines were collected during 2017-2020; of which 45 were positive for CIAV nucleic acid, with a positive rate of 8.08%. Our results showed that genome sequence similarity among a total of 12 CIAV isolates was high, and ranged from 97.1% to 99.3%, and their similarity to the vaccine strains Cux-1 and Del-Ros ranged from 97.8% to 98.6%. However, There were non-synonymous amino acid mutations in the locus of the major capsid proteins VP1, VP2 and VP3 among all isolates. The subsequent sequence analysis indicated that the isolates of HN-4 and HN-8 showed genetic recombination and follow up animal experiments revealed that HN-4 might be a pathogenic strain. Our results reveal that both field infection and non-CIAV vaccines contamination promote the epidemiology of CIAV in China and some dominant epidemic viruses have undergone recombination and evolution. This study provides important information to help with the prevention and control of CIAV in the poultry industry.